The Guided School Fitness Model: Confidence (CAPL-2) as the Mediator of Behaviour Change in Inactive Schoolchildren - Bano, Asia; Hafiz, Eliza; Hanim Hamza , Sareena; Ahmed Jam , Farooq (International Journal of Sport Studies for Health, 2026)
Objective: This study aims to examine the Guided School Fitness Model, especially the Functional Training Program (FTP). Methods and Materials: Functional Training Program (FTP) used as an intervention to increase physical activity behavior (PAB) in inactive schoolchildren. Based on Self-determination Theory (SDT), the authors hypothesized that FTP’s effect on PAB would be mediated through changes in schoolchildren’s confidence, exercise retention, and knowledge & understanding. Results: The FTP had a significant positive effect on confidence (β=0.624), exercise retention (β=0.755), and knowledge & understanding (β=0.684). All three mediators positively influenced PAB: confidence (β=0.543), exercise retention (β=0.498), and knowledge & understanding (β=0.571) improved physical activity behavior. Importantly, the mediation analysis confirmed that the FTP’s effect on PAB is mediated by these three variables. The indirect effect from the mediation analysis via confidence (β=0.486), exercise retention (β=0.522), and knowledge & understanding (β=0.448) were all statistically significant, demonstrating specific pathways of behavior change. It also demonstrated that the model significantly explained a portion of the variance in PAB, indicating high predictive strength. Conclusion: These findings indicate that successful interventions need to be holistic and address not only physical activity but also aspects such as confidence, long-term participation, and health literacy to achieve sustainable behavior change in inactive children.